Clinical significance of sequestration in adults with severe malaria. - Dondorp, A (2008)
Reduced microcirculatory flow is a fundamental feature in the pathophysiology of severe Plasmodium falciparum malaria and sequestration of red blood cells containing mature parasites is considered a central cause of this. Direct microscopic observation of the microcirculation in the living patient with severe malaria has enabled us to quantify this phenomenon and link it to severity of disease, supporting the findings of pathology studies. Moreover, the sequestered parasite biomass, calculated from parasite derived plasma PfHRP2 concentrations, strongly correlates with disease severity. Artesunate prevents sequestration by killing ring form parasites, aborting their maturation, which can explain the mortality benefit of this drug compared to quinine in the treatment of adult severe malaria. Levamisole is currently tried as adjunctive treatment in severe malaria targeting sequestration.